On control of transport in Brownian ratchet mechanisms. (March 2015) - Roychowdhury, Subhrajit; Saraswat, Govind; Salapaka, Srinivasa; Salapaka, Murti
Abstract : Highlights: Systematic method to maximize velocity/efficiency of Brownian ratchets in open-loop. Quantitative estimation of pdf of transport and error bounds on back propagation. Optimal strategy to maximize efficiency in closed-loop for Brownian ratchets. Up to three times improvement in efficiency over open-loop method. Up to 35% improvement in efficiency over closed-loop methods that maximize velocity. Abstract: Engineered transport of material at the nano/micro scale is essential for the manufacturing platforms of the future. Unlike conventional transport systems, at the nano/micro scale, transport has to be achieved in the presence of fundamental sources of uncertainty such as thermal noise. Remarkably, it is possible to extract useful work by rectifying noise using an asymmetric potential; a principle used by Brownian ratchets. In this article a systematic methodology for designing open-loop Brownian ratchet mechanisms that optimize velocity and efficiency is developed. In the case where the particle position is available as a measured variable, closed loop methodologies are studied. Here, it is shown that methods that strive to optimize velocity of transport may compromise efficiency. A dynamic programming based approach is presented which yields up to three times improvement in efficiency over optimized open loop designs and 35% better efficiency over reported closed loop strategies that focus on optimizing velocities.